2011
DOI: 10.1051/0004-6361/201015579
|View full text |Cite
|
Sign up to set email alerts
|

Gran Telescopio Canarias OSIRIS transiting exoplanet atmospheric survey: detection of potassium in XO-2b from narrowband spectrophotometry

Abstract: We present Gran Telescopio Canarias (GTC) optical transit narrowband photometry of the hot-Jupiter exoplanet XO-2b using the OSIRIS instrument. This unique instrument has the capabilities to deliver high-cadence narrowband photometric lightcurves, allowing us to probe the atmospheric composition of hot Jupiters from the ground. The observations were taken during three transit events that cover four wavelengths at spectral resolutions near 500, necessary for observing atmospheric features, and have near-photon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
138
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 56 publications
3
138
0
Order By: Relevance
“…HST/NICMOS has been used to detect H 2 O and CH 4 (Swain et al 2008), though the H 2 O feature has been challenged by a more sensitive search using filter photometry (Sing et al 2009;Désert et al 2009Désert et al , 2010 showing the presence of haze condensate at high altitude as previously observed in the optical using HST/ACS (Pont et al 2008;Lecavelier des Etangs et al 2008a). In addition to HST, groundbased, high-resolution spectra have also allowed sodium detection in HD 189733 b (Redfield et al 2008), confirmed sodium in HD 209458 b (Snellen et al 2008), detected CO and even winds in the planetary atmosphere (Snellen et al 2010), while the other important alkali metal potassium has been detected in XO-2b using narrowband photometry (Sing et al 2011). Sing et al (2008a) revisited all the existing HST/STIS spectroscopic data of HD 209458 b transits gathered over the years.…”
Section: Introductionmentioning
confidence: 99%
“…HST/NICMOS has been used to detect H 2 O and CH 4 (Swain et al 2008), though the H 2 O feature has been challenged by a more sensitive search using filter photometry (Sing et al 2009;Désert et al 2009Désert et al , 2010 showing the presence of haze condensate at high altitude as previously observed in the optical using HST/ACS (Pont et al 2008;Lecavelier des Etangs et al 2008a). In addition to HST, groundbased, high-resolution spectra have also allowed sodium detection in HD 189733 b (Redfield et al 2008), confirmed sodium in HD 209458 b (Snellen et al 2008), detected CO and even winds in the planetary atmosphere (Snellen et al 2010), while the other important alkali metal potassium has been detected in XO-2b using narrowband photometry (Sing et al 2011). Sing et al (2008a) revisited all the existing HST/STIS spectroscopic data of HD 209458 b transits gathered over the years.…”
Section: Introductionmentioning
confidence: 99%
“…One way to mitigate these issues is by using ground-based highdispersion spectroscopy. For example, detections of sodium and potassium have been presented in the optical (Redfield et al 2008;Snellen et al 2008;Sing et al 2011a;Wood et al 2011;Jensen et al 2011;Zhou & Bayliss 2012;Wyttenbach et al 2015), and detections of carbon monoxide and water in the infrared (Brogi et al 2012(Brogi et al , 2014Rodler et al 2012;de Kok et al 2013;Birkby et al 2013;Lockwood et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, signatures from the atmospheres of hot-Jupiters have been detected Photometric time series are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/538/A46 in transmission spectra, both from atoms, including sodium (e.g. Charbonneau et al 2002;Snellen et al 2008;Redfield et al 2008), potassium (Sing et al 2011a;Colon et al 2012), hydrogen (Vidal-Madjar et al 2003), carbon (Vidal-Madjar et al 2004) and oxygen (Vidal-Madjar et al 2004), as well as from molecules such as water (Tinetti et al 2007), although this is disputed by Désert et al (2009), methane (Swain et al 2008), which has been challenged by Sing et al (2009) and Gibson et al (2011), and carbon monoxide (Snellen et al 2010). In addition, a gradual increase of the planet-to-star radius ratio of HD 189733b has been detected toward shorter wavelengths, which has been attributed to the scattering by haze particles (Pont et al 2008;Sing et al 2011b).…”
Section: Introductionmentioning
confidence: 99%